2012
DOI: 10.1159/000338249
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Parameters of Radiofrequency Coagulation on Volume of Stereotactic Lesion in Pallidotomy and Thalamotomy

Abstract: Background: One of the many reasons why lesional surgery for movement disorders has been more or less abandoned may have been the difficulty in predicting the shape and size of the stereotactic radiofrequency (RF) lesion. Objectives: To analyse the contribution of various RF coagulation parameters towards the volume of pallidotomies and thalamotomies. Methods: The relationship between temperature of coagulation, length of coagulated area and duration of coagulation on the one hand, and lesion volume on the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…According to the literature, the size of a thalamotomy lesion differs from one individual to other and is unpredictable, even when performed under constant thermocoagulation parameters [15]. It ranges from no lesion [16] to a 177-mm 3 lesion, with mean values varying from 26 to 74.5 mm 3 [15,16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, the size of a thalamotomy lesion differs from one individual to other and is unpredictable, even when performed under constant thermocoagulation parameters [15]. It ranges from no lesion [16] to a 177-mm 3 lesion, with mean values varying from 26 to 74.5 mm 3 [15,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…It ranges from no lesion [16] to a 177-mm 3 lesion, with mean values varying from 26 to 74.5 mm 3 [15,16,17]. The volume of the thalamotomy lesion, measured in our patient with a fine-cut CT scan and MRI 10 years after the thalamotomy procedure, was about 269.6 mm 3 (4.65 mm in length, 5.73 mm in width, 10.12 mm in height), which is larger than the maximal estimated anatomical volume of the VPM nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,6,21 Literature on radiofrequency thalamotomy has suggested that while treatment parameters correlate with some of the lesion characteristics, these alone could not predict lesion volume, likely due to individual variation. 12 Sonication parameters needed to achieve goal temperatures and clinical effects vary between patients due to individual variation in factors, such as skull characteristics. 2 In this series, to achieve the desired clinical effect, patients had anywhere between 2 and 7 suprathreshold sonications (10 seconds each) and a total of 15-28 sonications (including subthreshold).…”
mentioning
confidence: 99%
“…(17) Another area where optical techniques have been introduced as intraoperative guidance tools is during stereotactic and functional neurosurgery. In functional neurosurgery, a small area of the brain is altered either by radiofrequency (RF) lesioning, i.e., thermal coagulation, (18,19) deep brain stimulation (DBS), (20,21) or cell-line implantation. (22,23) Of these named methods, DBS is the method most commonly used today, with more than 120000 lead implantations worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…(29) During stereotactic neurosurgery, impedance measurements are often performed in relation to RF lesioning, i.e., coagulation of a small brain region in the pallidum or thalamus to alleviate movement disorders. (19) The principle is similar to DBS, i.e., that the cluster of nerves creating the symptoms are affected. However, due to the irreversible effect of the RF technology, many clinical centers prefer to use DBS instead.…”
Section: Introductionmentioning
confidence: 99%